Significance of miR-27a and miR-31 in early diagnosis and prognosis of colorectal cancer - Cui, Qingjun (Oncol Lett, 2019)
Clinical significance of micro-ribonucleic acid (miR)-27a and miR-31 in the early diagnosis and prognosis of colorectal cancer were investigated. Forty patients with colorectal malignancy admitted to Xintai People's Hospital from February 2014 to April 2018 were enrolled as the observation group, of which 30 patients were diagnosed via pathological biopsy. Another 40 patients diagnosed with colorectal polyp and receiving surgical treatment were selected as the control group. The relative amount of miR-27a and miR-31 was measured. The relative expression levels of miR-27a and miR-31 in patients were analyzed. The diagnostic sensitivity, specificity and accordance rates of positive miR-27a and miR-31 expression in colorectal cancer were recorded. The correlation of the relative expression levels of miR-27a and miR-31 with the survival time of patients were analyzed. In the observation group, the relative expression levels of miR-27a and miR-31 in patients with lymph node metastasis and distant metastasis were higher than those in patients without lymph node metastasis and distant metastasis (P<0.05). Histological type of patients with non-mucinous carcinoma had increased relative expression levels of miR-27a and miR-31 in comparison with those with mucinous carcinoma (P<0.05). In terms of Duke's grade, the relative expression levels of miR-27a and miR-31 in patients with grade C and D were higher than those in patients with grade A and B (P<0.05). The diagnostic sensitivity, specificity and accordance rate of positive miR-27a expression were lower than those of positive miR-31 expression. The relative expression levels of miR-27a and miR-31 were positively correlated with the survival time of patients (P<0.05). The expression levels of miR-27a and miR-31 are related to distant metastasis and tumor grade of patients with colorectal cancer, and positively associated with the survival time of patients, having high diagnostic value.